LOW TEMPERATURE SILCORE DEPOSITION OF UNDOPED AND DOPED SILICON FILMS - Safarmatov Uchqun Sohibjon o‘g‘li (World Scientific Research Journal, 2025)
The use of ultra-shallow junctions and high-k gate dielectric materials has resulted in a demand for lower thermal budget processing by device manufacturers (1-3). This requires that low temperature processes must be found to replace longstanding higher temperature process steps and enable new applications for novel integration flows. In this paper, a low temperature amorphous silicon process based on Silcore® chemistry is described. Silcore is a proprietary ASM™ version of purified trisilane Si3H8, manufactured by Voltaix. This process has been demonstrated for low pressure chemical vapor deposition (LPCVD) undoped amorphous silicon films and phosphorous-doped amorphous silicon films in a vertical furnace. Deposition of undoped, phosphorous, arsenic, and boron-doped amorphous, polycrystalline, or epitaxially deposited Si or SiGe films has also been performed in a single-wafer reactor. Silcore offers the possibility of reaching higher deposition rates than silane at lower deposition temperatures. This feature makes silcore an attractive candidate for the semiconductor device industry from the standpoint of thermal budget and cost of ownership considerations. In this paper, we will describe the results of studies performed examining silcore-based chemistry to obtain amorphous, polycrystalline, and epitaxial films. These experiments are performed for two hardware configurations: a LPCVD vertical furnace and a single wafer reactor capable of epitaxial deposition. While the silcore chemistry is the same for the two configurations discussed, the deposition is occurring in two different regimes: a thermal/kinetic regime in the vertical furnace and a mass-flow limited regime in the single wafer reactor. Initial results for dependence of the deposition results on temperature, pressure, and doping are described. Further observations regarding film properties, such as uniformity and surface roughness will also be described.